2022
DOI: 10.1007/s10904-022-02236-w
|View full text |Cite
|
Sign up to set email alerts
|

Structural Elucidation and Electrochemiluminescence on a 3D Cadmium(II) MOF with 5-c Topology

Abstract: A novel cadmium (II) based MOF, [Cd(μ-ppza)] n (1) (H 2 ppza = 3-(pyridin-4-yl)-1H-pyrazole-5carboxylic acid) was synthesized under solvothermal condition. The single-crystal X-ray diffraction reveals that the title MOF 1 exhibits a 3D structure bridged through the carboxylic group, which has a 5-c {4 6 .6 4 } topological structure. Furthermore, MOF 1 exhibits good electrochemiluminescence (ECL) behavior.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…[39] The anodic peak at about 0.26 V and the cathodic peak at about 0.11 V might correspond to the redox reaction between Co 2 + and Co 3 + and the probable charge transfer mechanism are as follows: [40,41] CoðIIÞ s þ OH À $ CoðIIÞðOHÞ ad þ e À CoðIIÞðOHÞ ad $ CoðIIIÞðOHÞ ad þ e À Similar reversible faradaic reaction has appeared in other reported MOF-based electrode materials, such as Ni 3 (btc) 2 • 12H 2 O [42] and [CoCo 0.5 Co 0.5 (μ-ppa) 2 (H 2 O) 3 ] n . [31] The GCD curves of SEU-1 at various current densities (1 to 5 A g À 1 ) in the potential window of 0 to 0.4 V (vs. SCE) are presented in Figure 7a. An obvious slope change appeared near 0.15 V in the shape of discharge curves further confirms the typical pseudocapacitance behavior of the SEU-1 electrode, which is in well accordance with CV results.…”
Section: Powder X-ray Diffraction (Pxrd) and Thermogravimetric Analys...mentioning
confidence: 99%
See 1 more Smart Citation
“…[39] The anodic peak at about 0.26 V and the cathodic peak at about 0.11 V might correspond to the redox reaction between Co 2 + and Co 3 + and the probable charge transfer mechanism are as follows: [40,41] CoðIIÞ s þ OH À $ CoðIIÞðOHÞ ad þ e À CoðIIÞðOHÞ ad $ CoðIIIÞðOHÞ ad þ e À Similar reversible faradaic reaction has appeared in other reported MOF-based electrode materials, such as Ni 3 (btc) 2 • 12H 2 O [42] and [CoCo 0.5 Co 0.5 (μ-ppa) 2 (H 2 O) 3 ] n . [31] The GCD curves of SEU-1 at various current densities (1 to 5 A g À 1 ) in the potential window of 0 to 0.4 V (vs. SCE) are presented in Figure 7a. An obvious slope change appeared near 0.15 V in the shape of discharge curves further confirms the typical pseudocapacitance behavior of the SEU-1 electrode, which is in well accordance with CV results.…”
Section: Powder X-ray Diffraction (Pxrd) and Thermogravimetric Analys...mentioning
confidence: 99%
“…[29] Feng et al reported 2D layered Nibased and Co-based MOFs exhibiting a large specific capacitance of 184 and 134.5 F g À 1 , correspondingly. [30,31] Accordingly, we fabricate a 2D Co-based MOF directly used as an excellent cycling stability electrode material for SCs.…”
Section: Introductionmentioning
confidence: 99%